The Effect of The Problem Based Learning on Students Science Process Skills in Learning Physics: A Meta Analysis - Nazifah, Naurah; Amir, Hafizana Tiara; Hidayatullah, Silmi (Jurnal Pendidikan MIPA, 2022)
Revolution 4.0 requires humans to have 21st century skills. The 21st century guides human resources that are able to compete with the wider community, so the government seeks to improve human resources through education. Thinking skills that are expected to achieve optimal learning outcomes are science process skills, because with these thinking skills students will be able to build meaning and confirm their understanding of a physical concept symptom and emphasize the importance of direct experience involvement in the learning process. The learning model that emphasizes learning as a process that involves solving problems in an actual context is the Problem based Learning model. Based on the description above, it can be stated that there are several researchers who have conducted research on the effect of problem based learning models on students' science process skills. So a meta-analysis of 15 articles was carried out, there was a significant effect of the problem based learning model on students' science process skills in learning physics based on grade level, physics subject matter and student learning outcomes. Keywords: problem based learning, science process skills, physics. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp651-660